Identifikasi Telajakan di Desa Pakraman Nyuh Kuning, Kecamatan Ubud Kabupaten Gianyar - MAHARDIKA, I KETUT GDE MAYUN; SUDARSANA, A.A. GEDE DALEM; SUGIANTHARA, A.A. GEDE (Jurnal Arsitektur Lansekap, 2016)
ABSTRACT Telajakan Identification in Desa Pakraman Nyuh Kuning, Kecamatan Ubud Kabupaten Gianyar The customary village or desa pakraman of Nyuh Kuning located in the administrative village of Mas Village, Ubud District, Gianyar Regency, and is bounded by several natural and cultural tourism places. The village which is located in tourism centers usually threatened by traditional degradation such as the lost of telajakan or front yard garden. In contrary, telajakan still preserved in desa pakraman Nyuh Kuning. The aims of the study were to investigate the function and development of telajakan in Nyuh Kuning and the commitment villagers in managing telajakan. Some methods were used such as questionnaire surveys, interviews, observations and literature study. The results showed that 75% of respondents knew the function and consider to the development of telajakan and it develop into different sizes, forms, and functions. The structure of telajakan were dominated by flowers i.e. frangipani (88%); gardenia (3%); bougainvillia (2%); roses (2%); and hibiscus (5%). The respondents motivation to preserved and manage telajakan in order to keep Nyuh Kuning become tourism destination. Keywords: telajakan, desa pakraman Nyuh Kuning, Ubud